2021
DOI: 10.3390/ma14020445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Notch-to-Depth Ratio on the Post-Cracking Behavior of Steel-Fiber-Reinforced Concrete

Abstract: Concrete barely possesses tensile strength, and it is susceptible to cracking, which leads to a reduction of its service life. Consequently, it is significant to find a complementary material that helps alleviate these drawbacks. The aim of this research was to determine analytically and experimentally the effect of the addition of the steel fibers on the performance of the post-cracking stage on fiber-reinforced concrete, by studying four notch-to-depth ratios of 0, 0.08, 0.16, and 0.33. This was evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…The performance of the bio-based repair mortar was studied through restrained shrinkage and pull-out tests [25]. Valdez Aguilar et al (2021) [23] presented a detailed review on the various types of bacteria used for healing concrete and discussed the different concrete properties affected by the addition of bacteria. Vijay and Kunamineni et al (2019) [27] used cultured bacillus subtilis in spore powder form and culture form in mortar concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the bio-based repair mortar was studied through restrained shrinkage and pull-out tests [25]. Valdez Aguilar et al (2021) [23] presented a detailed review on the various types of bacteria used for healing concrete and discussed the different concrete properties affected by the addition of bacteria. Vijay and Kunamineni et al (2019) [27] used cultured bacillus subtilis in spore powder form and culture form in mortar concrete.…”
Section: Introductionmentioning
confidence: 99%
“…12 Lacidogna et al 13 attempted to study damage in concrete beams using DIC technique. The influence of the notch-to-depth ratio on the postcracking behaviour of SFRC beams was investigated by Aguilar et al 14 Rao and Rao 15 reported the toughness indices of FRC subjected to mode II loading in a different investigation.…”
Section: Introductionmentioning
confidence: 99%